Probiotic Supplementation Regulates Placental and Fetal Development in C57BL6/J Mice (P20-008-19). (13th June 2019) - Larson, Kate; Krout, Danielle; Alvine, Travis; Zeng, Huawei; Bundy, Amy; Klurfeld, David; Solano-Aguilar, Gloria; Bukowski, Michael; Meydani, Simin; Roemmich, James
Abstract: Objectives: Maternal high-fat (HF) diet predisposes offspring to metabolic syndrome, in part, by inducing alterations during placental development resulting in abnormal fetal development and offspring birth weight. We previously reported in a rat model that a maternal malnutrition diet increases fetal inflammation, and placental vascularization, and decreases offspring birth weight followed by adult-onset obesity. In the current study, we investigated when during gestational development a maternal HF diet induces changes in placental weight, lipid content, and inflammation. We further investigated whether probiotic supplementation offsets HF-diet induced adverse outcomes. Methods: Two-month old female C57BL/6 mice were fed diets of 16% fat (normal-fat, NF) or 45% fat (high-fat, HF) for 8 weeks followed by 4 weeks of probiotic ( Bifidobacterium animalis subsp. lactis, BB-12) supplementation. Fetuses and placentae were examined mid- (D12) and late- (D19) gestation Results: Placental length, width, and weight as well as fetal weight were decreased in the HF group at D12. Probiotic supplementation reversed the HF diet-induced reduction in placental weight at D12. These beneficial effects of probiotic supplementation were absent at D19 as fetal weights from all HF diet fed groups weighed less regardless of probiotic supplementation. Probiotic supplementation reduced placental TNF-alpha mRNA at D12 and IL-10 mRNA at D19. Triacylglyceride concentration was increased at D19 by HF diet, in part, by the preceding increases in lipoprotein lipase (LPL) and plasma membrane-associated fatty-acid binding protein (FABPpm) mRNA expression at D12. Conclusions: These findings suggest that maternal HF diet alters placental size and weight as well as fetal weight and that probiotic supplementation renders a protective effect against these changes in mid-gestation. Future studies are needed to determine whether the protective mechanism of probiotic supplementation in mid-gestation has beneficial effects on offspring developmental programming. Funding Sources: USDA Agricultural Research Service Project #3062-51000-052-00D.